Testing or transforming practice: probing an Icelandic national initiative to improve literacy education. (20th February 2017) - Sigþórsson, Rúnar
Abstract : In the wake of a White Paper on Education Reform, published in 2014 by the Icelandic Ministry of Education, Science and Culture, the minister launched a national initiative to improve literacy education in Icelandic compulsory schools. The White Paper and the national initiative came as a reaction to the disappointing performance of 15‐year‐olds on the Programme for International Student Assessment (PISA) test 2012. The aim of this paper is to critique the national initiative, the policy behind it and its implementation, in light of definitions of literacy and literacy teaching as a pedagogical activity and some critical issues of literacy education in Icelandic compulsory schools. These include a low proportion of students on the two highest performance levels of the Programme for International Student Assessment (PISA) results, gender differences, residential differences and differences between social groups, and diminishing book reading of children and teenagers. The main conclusion is that the national initiative is characterised by a narrow focus on testing reading literacy and recording data to compare students with test standards but lacks a rational and coherent plan to address the critical issues of literacy education mentioned earlier, the professional development of teachers and the development of schools as professional learning communities.